An in situ generated amorphous CoFePi and crystalline Ni(PO3)2 heterojunction as an efficient electrocatalyst for oxygen evolution. Issue 48 (30th November 2018) - Liu, Dong-Cheng; Cao, Li-Ming; Luo, Zhi-Mei; Zhong, Di-Chang; Tan, Jing-Bo; Lu, Tong-Bu
Abstract : Engineering efficient and cost-effective electrocatalysts for the oxygen evolution reaction (OER) is an essential part of electrochemical water splitting. Abstract : Engineering efficient and cost-effective electrocatalysts for the oxygen evolution reaction (OER) is an essential part of electrochemical water splitting. Herein, we report the in situ preparation of an efficient OER electrocatalyst CoFePi/Ni(PO3 )2 on carbon cloth (CC) by decorating amorphous CoFe phosphate (CoFePi) on crystalline nickel phosphate (Ni(PO3 )2 ). The as-synthesized hierarchically heterogeneous electrocatalyst can be directly used as a working electrode for the OER without extra substrates or binders. Electrocatalytic studies showed that the CoFePi/Ni(PO3 )2 /CC electrode displays excellent OER catalytic activity and stability. A current density of 10 mA cm −2 during the OER process can be achieved at a low overpotential of 213 mV in 1.0 M KOH solution, comparable to the results reported for the most efficient OER electrocatalysts. The ultrahigh oxygen evolution activity and high durability are ascribed to the unique 3D hierarchical heterogeneous nanostructure and in situ generated amorphous–crystalline composite, as well as the highly conductive substrate of CC, which endows the composite catalyst with sufficient active sites, strong structural stability and good electrical conductivity. This strategy offers a new direction to fabricate high-performance electrocatalysts for the oxygen evolution reaction.